Architectures for Next Generation EU Cities Challenges, Key Drivers, and Research Trends - ANTONINI, ERNESTO (Ricerche di tecnologia dell'architettura, 2022)
Cities are facing unprecedented challenges driven by different forces. On the one hand the ever-increasing effects of climate change are impacting on the urban microclimate and environmental balance, on the other one social, political and economic issues are influencing the living conditions, the accessibility to primary services and resources, as well as growth opportunities for the younger generations. The rise of a social awareness regarding these topics suggests how relevant scientific-based evidence could be and calls for additional efforts to bridge the gap between science and society, in order to stimulate a collective responsibility and due actions. The complex interaction among these factors inspired a forward-looking reflection not only on key drivers of change but also on possible future trends for research assuming an interdisciplinary and multiscale perspective. The book collects several experiences from different contributors working in many contexts and countries, but sharing the same projection to the future. Four key priorities are addressed: the resilience to climaterelated events and impacts, the energy issue with reference to both the advances at building level and the role of end users, the capacity to adapting components and systems to emerging needs, and the adoption of assessment and simulation tools for improving the design capacity within a circular system perspective. The book provides therefore insights, experiences, approaches to deal with current and especially with future transition processes which are expected to shape the cities of tomorrow. Thus, its ambition is not to provide definitive answers but to become a starting point for exploring promising research pathways for the next generation cities.